Optical control of cell differentiation on synthetic collagen-like scaffolds. Issue 13 (2nd September 2019) - Kobayashi, Mime; Honda, Ryosuke; Ando, Tsuyoshi; Tanihara, Masao
Abstract: We have developed biocompatible scaffolds that enable cell fate control with visible light. The scaffolds are based on synthetic collagen-like polypeptide, poly(prolyl-hydroxyprolyl-glycyl) poly(Pro-Hyp-Gly) which has been used for cosmetics and other healthcare applications. Bioactive peptides were conjugated to the scaffolds via photoactivation reaction utilizing 488 nm visible light. In addition, the use of a photocleavable crosslinker enables dissociation of chemical moieties by 405 nm laser irradiation. The synthesis scheme enables optical control to attach and detach functional peptides in pre-patterned shapes. Using bone forming peptide (BFP), we demonstrate that calcium deposition by rat bone stromal cells can be directed on the scaffold. Using other signaling molecules and three-dimensional scaffolds, controlled differentiation of stem cells can be achieved by spatio-temporally specific irradiation of confocal microscope laser.